1981
DOI: 10.1111/j.1365-2230.1981.tb02289.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy and atopic eczema I

Abstract: In recent years there has been an encouraging increase in interest in atopic eczema, particularly in relation to its immune logical aspects, and as a result there have been considerable advances in our understanding of the disease. Nevertheless, the relationship of the immunological derangements observed to the disease remains unclear. This relationship will be the principal subject of this review, which will be published in two parts. In the first, genetic and environmental factors predisposing to atopy and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The fact that all of the patients with gastroenteritis healed while receiving standard cow's milk formulas and that none developed cow's milk allergy indicates that an increased gut permeability is not necessarily deleterious. Intestinal macromolecular absorption is thought to be increased in infantile eczema (3). Our results are in agreement with the latter hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The fact that all of the patients with gastroenteritis healed while receiving standard cow's milk formulas and that none developed cow's milk allergy indicates that an increased gut permeability is not necessarily deleterious. Intestinal macromolecular absorption is thought to be increased in infantile eczema (3). Our results are in agreement with the latter hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…4, No. 3,1985 celiac patients showing normalized gut histological findings is in favor of this hypothesis (5). Supporting our own data, Jackson et al showed the presence of an increased gut permeability to polyethyleneglycol in adult patients with eczema (4).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This commonly used g e n e ra liza tion is tru e fo r a lle r g ic r h i n i t i s and a lle r g ic asthma but not fo r atopic derm ati t i s . The d e rm a titis which occurs in atopies is not a ty p ic a l atop ic disease since the importance of a lle r g ic fa c to rs is uncertain (20)(21)(22). Approximately 20% of p a tie n ts w ith severe fle x u ra l eczema have normal serum IgE le v e ls (22).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…We believe that this system may have broken down in individuals with atopic eczema, and that their skin disease arises as a direct consequence of defective handling of normally harmless dietary antigens. It now seems likely that atopy arises as a consequence of genetically determined immunodeficiency {see Atherton, 1981) which leads to the development of a quantitatively abnormal IgE response to common antigens, including food antigens. Rats which have been sensitized reaginically to food antigens by the parenteral route subsequently demonstrate enhanced gastro-intestinal absorption of the same antigens given orally.…”
mentioning
confidence: 99%